2023
DOI: 10.1111/1462-2920.16334
|View full text |Cite
|
Sign up to set email alerts
|

Selective and differential feeding on marine prokaryotes by mucous mesh feeders

Abstract: Microbial mortality impacts the structure of food webs, carbon flow, and the interactions that create dynamic patterns of abundance across gradients in space and time in diverse ecosystems. In the oceans, estimates of microbial mortality by viruses, protists, and small zooplankton do not account fully for observations of loss, suggesting the existence of underappreciated mortality sources. We examined how ubiquitous mucous mesh feeders (i.e. gelatinous zooplankton) could contribute to microbial mortality in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
2
1
0
Order By: Relevance
“…This larger contribution of nanoplanktonic prey was also true of the salps from Cycles 3 and 4, although the contribution of microplankton in the prey field during these cycles was lower than in Cycle 1. While these observations may support growing evidence in favor of selective feeding in salps (von Harbou et al 2011;Metfies et al 2014;Dadon-Pilosof et al 2019;Pauli et al 2021;Thompson et al 2023), similar differences in prey contributions for doliolids have been linked to small-scale heterogeneity in the prey community due to micro patches and thin layers (Takahashi et al 2015;Walters et al 2019;Greer et al 2020;Frischer et al 2021). Our vertically-integrated ambient prey abundances fundamentally average over these fine-scale features.…”
Section: Ecological Implicationssupporting
confidence: 76%
See 1 more Smart Citation
“…This larger contribution of nanoplanktonic prey was also true of the salps from Cycles 3 and 4, although the contribution of microplankton in the prey field during these cycles was lower than in Cycle 1. While these observations may support growing evidence in favor of selective feeding in salps (von Harbou et al 2011;Metfies et al 2014;Dadon-Pilosof et al 2019;Pauli et al 2021;Thompson et al 2023), similar differences in prey contributions for doliolids have been linked to small-scale heterogeneity in the prey community due to micro patches and thin layers (Takahashi et al 2015;Walters et al 2019;Greer et al 2020;Frischer et al 2021). Our vertically-integrated ambient prey abundances fundamentally average over these fine-scale features.…”
Section: Ecological Implicationssupporting
confidence: 76%
“…Although traditional microscopic analyses of salp stomach contents have long supported their non-selective nature (Silver 1975; Vargas and Madin 2004; Tanimura et al 2008), these methods are limited in terms of image resolution such that only large, hard-bodied plankton can be easily identified. Modern tracer and genetic analyses have also been applied to gut contents to determine relative proportions of different types of prey (von Harbou et al 2011; Metfies et al 2014; Pauli et al 2021; Thompson et al 2023) and are beginning to challenge the existing paradigm of non-selectivity, as these studies more often find differences between prey types available and those found in the guts. However, these methods do not allow for determining prey size.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Prochlorococcus and Synechococcus are similar in size and both roughly spherical but they experienced divergent capture rates in this study (Figs. 2 and 4 ), consistent with previous studies of gelatinous grazers ( 23 ). Surface properties of particles, including hydrophobicity, have also been shown to mediate particle capture ( 74 , 76 ).…”
Section: Discussionsupporting
confidence: 92%